STIM Proteins and Orai Ca2+ Channels Are Involved in the Intracellular Pathways Activated by TLQP-21 in RAW264.7 Macrophages - Molteni, Laura; Rizzi, Laura; Bresciani, Elena; Meanti, Ramona; Fehrentz, Jean-Alain; Verdié, Pascal; Omeljaniuk, Robert J.; Biagini, Giuseppe; Locatelli, Vittorio; Torsello, Antonio (Frontiers in Pharmacology, 2018)
TLQP-21 is a neuropeptide which has been implicated in regulation of nociception and other relevant physiologic functions. Although recent studies identified C3a and gC1q receptors as targets for TLQP-21, its intracellular molecular mechanisms of action remain largely unidentified. Our aim was (i) to explore the intracellular signalling pathway(s) activated by JMV5656, a novel derivative of TLQP-21, in RAW264.7 macrophages, and (ii) to assess linkages of these pathways with its purported receptors. JMV5656 stimulated, in a dose-dependent fashion, a rapid and transient increase in intracellular Ca2+ concentrations in RAW264.7 cells; repeated exposure to the peptide resulted in a lower response, suggesting a possible desensitization mechanism of the receptor. In particular, JMV5656 increased cytoplasmic Ca2+ levels by a PLC-dependent release of Ca2+ from the endoplasmic reticulum. STIM proteins and Orai Ca2+ channels were activated and played a crucial role. In fact, treatment of the cells with U73122 and thapsigargin modulated the increase of intracellular Ca2+ levels stimulated by JMV5656. Moreover, in RAW264.7 cells intracellular Ca2+ increases did not occur through the binding of JMV5656 to the C3a receptor, since the increase of intracellular Ca2+ levels induced by JMV5656 was not affected by specific siRNA against C3aR. In summary, our study provides new indications for the downstream effects of JMV5656 in macrophages, suggesting that it could activate receptors different from the C3aR.